Pretreatment Technologies of Lignocellulosic Materials in Bioethanol Production Process - Hidayat, Mohamad Rusdi (Balai Riset dan Standardisasi Industri Pontianak, 2013)
Bioethanol is one type of biofuel that developed significantly. The utilization of bioethanol is not only limited for fuel, but also could be used as material for various industries such as pharmaceuticals, cosmetics, and food. With wide utilization and relatively simple production technology has made bioethanol as the most favored biofuel currently. The use of lignocellulosic biomass, microalgae, seaweeds, even GMO (Genetically modified organisms) as substrates for bioethanol production has been widely tested. Differences in the materials eventually led to change in the production technology used. Pretreatment technology in the bioethanol production using lignocellulosic currently experiencing rapid development. It is a key process and crucial for the whole next steps. Based on the advantages and disadvantages from all methods, steam explotion and liquid hot water methods are the most promisingÂ pretreatment technology available.